2018
DOI: 10.3892/etm.2018.6355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of dexmedetomidine on analgesic efficacy and inflammatory cytokines in patients undergoing laparoscopic surgery

Abstract: The effects of different doses of dexmedetomidine on analgesic efficacy and inflammatory cytokines in patients with laparoscopic surgery were investigated. A total of 179 laparoscopic patients from March 2015 to May 2017 were enrolled and randomly divided into the control group (group A) and three experimental groups with different doses of dexmedetomidine (group B: 0.25; group C: 0.5 and group D: 1 µg/kg). Results showed that there was no significant difference between the four groups in the operation time, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Wan et al administered 0.25, 0.5 and 1 μg/kg doses of dexmedetomidine to patients undergoing laparoscopic surgery with general anesthesia and examined CRP, TNF-α and IL-10 levels. Compared to the 0.25 μg/kg dose, patients receiving 0.5 and 1 μg/kg had lower CRP and TNF-α levels, while the IL-10 level was observed to be highest in the 1 μg/kg group (40). Based on this result, this may be a new research topic in terms of the effect of DEX on APAP toxicity and there is a need for new studies involving different dose applications.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Wan et al administered 0.25, 0.5 and 1 μg/kg doses of dexmedetomidine to patients undergoing laparoscopic surgery with general anesthesia and examined CRP, TNF-α and IL-10 levels. Compared to the 0.25 μg/kg dose, patients receiving 0.5 and 1 μg/kg had lower CRP and TNF-α levels, while the IL-10 level was observed to be highest in the 1 μg/kg group (40). Based on this result, this may be a new research topic in terms of the effect of DEX on APAP toxicity and there is a need for new studies involving different dose applications.…”
Section: Discussionmentioning
confidence: 71%
“…When the literature is examined, it is possible to see many molecules with therapeutic or preventive properties used in research about APAP toxicity (2,4,6). Dexmedetomidine is an effective agent used for sedation in intensive care and anesthesia administration with increasing use as an adjuvant (39,40,41). With antioxidant properties proven in many researches, DEX is understood not to have been used in experimental research related to APAP toxicity in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work also has suggested that medium dosage of dexmedetomidine cannot only effectively relieve the pain of laparoscopic patients but also regulate the secretion of inflammatory cytokines. 31 Endothelial cells, astrocytes, pericytes, and extracellular matrix integrity. 33 GFAP is a cytoskeletal protein of astrocytes and serum GFAP concentration is of great value in the diagnosis of brain injury or stroke and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a statistically signifcant difference in serum TNF‐α and IL‐10 was shown between the two groups, suggesting that dexmedetomidine could significantly reduce neuroinflammation of elderly patients with MCI. Prior work also has suggested that medium dosage of dexmedetomidine cannot only effectively relieve the pain of laparoscopic patients but also regulate the secretion of inflammatory cytokines 31 …”
Section: Discussionmentioning
confidence: 99%